Schrödinger’s Fetus and Relational Ontology: Reconciling Three Contradictory Intuitions in Abortion Debates - Milford, Stephen R. (Ethical theory and moral practice, 2024)
Pro-life and pro-choice advocates battle for rational dominance in abortion debates. Yet, public polling (and general legal opinion) demonstrates the public’s preference for the middle ground: that abortions are acceptable in certain circumstances and during early pregnancy. Implicit in this, are two contradictory intuitions: (1) that we were all early fetuses, and (2) abortion kills no one. To hold these positions together, Harman and Räsänen have argued for the Actual Future Principle (AFP) which distinguishes between fetuses that will develop into persons and those that will never develop into persons. However intellectually ingenious their solutions are, they fail to account for a third intuition: that the death of a wanted fetus - e.g. through termination or miscarriage - is of moral significance. Not only is this practically important, but it is also supported by public opinion. The authors of this paper argue that relational ontology can modify the AFP to better account for all three intuitions. Furthermore, it further emphasizes the pivotal role of the pregnant person who relates to their own fetus in either personal or impersonal ways. Addressing the fundamental challenges of relational ontology, the authors defend the position that human personal identity is ultimately relational.